Uji Efektifvitas Cendawan Mikoriza Lokal Gerogak Lahan Kering dan Komersial Pada Tanaman Jagung (Zea mays L.) - Julianus Jeksen (AGRICA, 2012)
Dryland in Indonesia has been dominated by acid soils, so that availability of phosphate (P) becomes the main obstacle in improving outcomes and only 10-30% of fertilizer P can be utilized by plants. One of the solution to meet the needs of phosphate is by utilization of mycorrhizal biofertilizer. These experiments were divided into several phases: 1) Looking for phases of mycorrhizal, 2) the laboratory analysis, 3) Testing phase on plants that were carried out by using polybags with sterile soil. The experiment was designed with a complete randomized block design (RAKL) by using a factor that consists of 6 treatments that are: 1) Without mycorrhizal inoculum (M0), 2) Mycorrhizal inoculum 5 g + 50 Spores (M5), 3) Mycorrhizal inoculum 10 g + 50 spores (M10), 4) Mycorrhizal inoculum 15 g + 50 spores (M15), 5) Mycorrhizal inoculum 20 g + 50 spores (M20), 6) Commercial mycorrhizal 10 g (Mk). All treatments were repeated four times so that the total 24 pot experiment. The experiment results show that mycorrhizal treatment given on the corn crop has very significant (P <0.01) to the number of leaf age of 35, 49, 63 days after, leaf wide have age 49 days after plant, fresh weight, oven-dry weight, absorb P, number of spores, mycorrhizal infection and significant effect (P <0.05) to plant height age of 35, 49, 63 day after plant, 63 days after plant, leaf wide, and P-available. Based on the results of this study will be suggested, in order to enhance the growth of corn plants can be used locally mikroiza a dose of 10 g + 50 spores.